Silicon-induced photosynthetic adaptations in common buckwheat under salt stress revealed by prompt chlorophyll a fluorescence analysis - Md. Rakib Hossain Raihan; Michal Antala; Marcin Stróżecki; Md. Intesaful Haque; Mirza Hasanuzzaman; Radosław Juszczak; Anshu Rastogi (Scientific Reports)
Abstract This study aimed at investigating the protective role of silicon (Si) in mitigating salt-induced damage in common buckwheat plants (Fagopyrum esculentum cv. Smuga). Twenty one-day-old seedlings were subjected to salt stress by irrigating 50 mM sodium chloride solutions for seven days, with or without Si (two foliar applications with 1 mM sodium metasilicate nonahydrate). Salt stress significantly altered the chlorophyll a fluorescence transient (OJIP) curve, disrupting energy flow and electron transport in photosystem II (PSII), as reflected in the O-J, J-I, and I-P phases, along with the emergence of a positive K-band indicating damage to the oxygen-evolving complex (OEC). Silicon application mitigated these effects, stabilizing the OEC and thylakoid membrane integrity while improving JIP test parameters and reducing excessive energy absorption, dissipation, and unregulated energy loss per reaction center. Silicon-treated plants under salt stress exhibited enhanced photochemical quenching, reduced regulatory energy dissipation, and decreased photosystem I (PSI) over-reduction. A significant increase in open PSI centers was observed, improving the balance and functionality between PSI and photosystem II. The application of Si resulted in significant photosynthetic improvements, which were also paired with enhanced morphological traits, such as increased root length and leaf thickness in saline conditions. Overall, findings indicate that exogenous Si helps to reduce salt-induced stress by enhancing photosynthetic efficiency in plants, positioning it as a promising strategy for improving crop performance in saline environments.